Feasibility of Telemedicine in Detecting Diabetic Retinopathy and Age-Related Macular Degeneration. (March 2015) - Vaziri, Kamyar; Moshfeghi, Darius M.; Moshfeghi, Andrew A.
Abstract Age-related macular degeneration and diabetic retinopathy are important causes of visual impairment and blindness in the world. Because of recent advances and newly available treatment modalities along with the devastating consequences associated with late stages of these diseases, much attention has been paid to the importance of early detection and improving patient access to specialist care. Telemedicine or, more specifically, digital retinal imaging utilizing telemedical technology has been proposed as an important alternative screening and management strategy to help meet this demand. In this paper, we perform a literature review and analysis that evaluates the validity and feasibility of telemedicine in detecting diabetic retinopathy and age-related macular degeneration. Understanding both the progress and barriers to progress that have been demonstrated in these two areas is important for future telemedicine research projects and innovations in telemedicine technology.